Zinc supplementation during pregnancy: a double blind randomised controlled trial. Issue 6703 (30th September 1989) - Mahomed, K.; James, D. K.; Golding, J.; McCabe, R.
Abstract : OBJECTIVE--To see whether zinc supplementation during pregnancy improves maternal and fetal outcome. DESIGN--Prospective study started at booking and continued till discharge of mother and baby from the maternity hospital. Mothers were randomly assigned to receive zinc supplementation or placebo in a double blind trial. SETTING--Mothers booking at one hospital. PATIENTS--Women booking before 20 weeks of gestation who agreed to take part in the study. 494 Mothers were followed up till the end of pregnancy. There was no difference between the groups given zinc and placebo in their social or medical backgrounds. INTERVENTIONS--Mothers in the active treatment group received one capsule of 20 mg elemental zinc daily and those in the placebo treated group a capsule identical in appearance and taste with the active capsule but which contained inert substances. MAIN OUTCOME MEASURE--Various adverse outcomes were tested, including maternal bleeding, hypertension, complications of labour and delivery, gestational age, Apgar scores, and neonatal abnormalities. The main outcome measure was birth weight. RESULTS--There were no differences whatsoever between mothers given a zinc supplement and those given a placebo. CONCLUSION--Zinc supplementation in pregnancy in the United Kingdom does not seem to offer any benefits to the mother or her fetus.